2022
DOI: 10.1007/s10096-022-04529-x
|View full text |Cite
|
Sign up to set email alerts
|

Human bocavirus-1 infections in Australian children aged < 2 years: a birth cohort study

Abstract: To determine human bocavirus-1 (HBoV1) infection characteristics in young Australian children. Data were from the Observational Research in Childhood Infectious Diseases (ORChID) study, a Brisbane, Australia–based birth cohort of healthy, term, newborns followed prospectively for 2 years. Parents recorded daily symptoms, maintained an illness-burden diary, and collected weekly nasal swabs, which were tested for 17 respiratory viruses, including HBoV1, by real-time polymerase chain reaction (PCR) assays. Main o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The EIA of IgG avidity has been developed to identify primary HBoV infection and immune activation [89]. ELISA techniques can find HBoV antibodies in serum using VLPs of VP1 and VP2 viruses [90,91]. Detecting HBoV infections can be made possible by immunofluorescence assays that look for IgG antibodies and biomarker-based assays [92][93][94].…”
Section: Diagnosis Of Hbovmentioning
confidence: 99%
“…The EIA of IgG avidity has been developed to identify primary HBoV infection and immune activation [89]. ELISA techniques can find HBoV antibodies in serum using VLPs of VP1 and VP2 viruses [90,91]. Detecting HBoV infections can be made possible by immunofluorescence assays that look for IgG antibodies and biomarker-based assays [92][93][94].…”
Section: Diagnosis Of Hbovmentioning
confidence: 99%
“…But approximately 40% cases of primary infection have <1 � 10 4 gc/mL during the initial phase of the symptomatic period and it has been observed that in some patients there is not correlation between high viral load in respiratory secretions (>10 6 gc/mL) and active infection (mRNA negative). 43,44,52,54,68,117,118 Detection of HBoV1 RNA in paediatric patients, rather than high viral load, has been associated with wheezing and pneumonia, thus it could be useful to identify active infection. 117,[119][120][121][122] An alternative for diagnosis in clinical practice could also be direct testing by antigen detection (immunofluorescence), 88 along with the respiratory panel.…”
Section: Detection and Diagnosis Of Hbov1mentioning
confidence: 99%
“…Some authors suggest that 1 × 10 4 –1 × 10 8 genome copies (gc) per mL of respiratory secretion indicate acute stage of infection. But approximately 40% cases of primary infection have <1 × 10 4 gc/mL during the initial phase of the symptomatic period and it has been observed that in some patients there is not correlation between high viral load in respiratory secretions (>10 6 gc/mL) and active infection (mRNA negative) 43,44,52,54,68,117,118 …”
Section: Detection and Diagnosis Of Hbov1mentioning
confidence: 99%
“…Most literature reported HBoV infection as prevalent in children between 6 months and 2 years with the highest detection rate during the second year [ 4 , 6 , 10 , 12 , 13 , 14 ], while it is rare (<5%) during the first 6 months of life [ 15 , 16 ]. Only in the study by Wang et al were children > 5 years the most affected, followed by children < 2 years and infants [ 1 , 15 , 16 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Although HBoV 2–4 variants have also been found in respiratory tract samples at lower frequencies, their role in the pathogenesis of respiratory infections is unclear. Moreover, HBoVs have been detected in urine [ 8 ], saliva [ 9 ], blood [ 10 , 11 ], tonsils [ 12 , 13 ], cerebrospinal fluid [ 14 ], and in environmental samples such as river water [ 15 ], sewage [ 16 , 17 ], and shellfish [ 18 ] with uncertain clinical significance.…”
Section: Introductionmentioning
confidence: 99%